Consumer Culture in Latin America
IX, 235 p. 7 illus.
Keywords: How can we understand consumption in a region known for its cultural richness and vast inequalities? What do Latin Americans consume, and why? Examining topics from tango and samba to sex workers in Costa Rica, from eating tamales to selling ice in the Andes, and from building and moving houses to buying cell phones, this collection brings together original research on some of the many forms of consumption and consumers that contribute to Latin American cultures and histories. Contributors include sociologists, anthropologists, media and cultural studies scholars, geographers and historians, showcasing diverse approaches to understanding Latin American consumption practices and consumer culture.